2019
DOI: 10.1002/dvg.23295
|View full text |Cite
|
Sign up to set email alerts
|

The testicular soma of Tsc22d3 knockout mice supports spermatogenesis and germline transmission from spermatogonial stem cell lines upon transplantation

Abstract: Spermatogonial stem cells (SSCs) are adult stem cells that are slowly cycling and self‐renewing. The pool of SSCs generates very large numbers of male gametes throughout the life of the individual. SSCs can be cultured in vitro for long periods of time, and established SSC lines can be manipulated genetically. Upon transplantation into the testes of infertile mice, long‐term cultured mouse SSCs can differentiate into fertile spermatozoa, which can give rise to live offspring. Here, we show that the testicular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 61 publications
(93 reference statements)
0
10
0
Order By: Relevance
“…As adult stem cells that produce spermatocytes, SSCs transmit genetic information to the next generation [ 4 , 5 ]. Studies have shown that SSCs can be cultured and passaged in vitro, and differentiate into sperm after transplantation [ 6 ]. Therefore, the study of SSCs is significant in terms of understanding the male germ cell differentiation mechanism, and has clinical application value in the treatment of male infertility [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…As adult stem cells that produce spermatocytes, SSCs transmit genetic information to the next generation [ 4 , 5 ]. Studies have shown that SSCs can be cultured and passaged in vitro, and differentiate into sperm after transplantation [ 6 ]. Therefore, the study of SSCs is significant in terms of understanding the male germ cell differentiation mechanism, and has clinical application value in the treatment of male infertility [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because all three intronic sequences do not include any known miRNAs or predicted stem-loop structures, they seem to act in trans as long ncRNA regulatory elements [20]. Similarly, constructs containing common selection markers/reporter genes like GFP, EGFP, Neo r , LacZ, and DsRed are often left within the target genome postselection [9,21,29,37,62]. However, these genes themselves can become potential targets of miRNAs of host origin, e.g., Mus musculus as discussed later.…”
Section: The Problemmentioning
confidence: 99%
“…Neomycin resistance gene (Neo r ) is one of the widely utilized selection markers for the cells which are correctly targeted, and the neomycin cassette itself is normally left within the genome post-selection, assuming that it has no adverse effect on the eukaryotic cell biology [21,50,62]. But upon careful observation, it can be seen that the Neo r gene construct itself is a potential target of several miRNAs of the eukaryotic origin or more specifically the miRNAs within the cells of the neomycin cassette containing transgenic mice (Table 1).…”
Section: Commonly Used Foreign Genes Targeted By Mus Musculus Mirnasmentioning
confidence: 99%
“…The genetic modification was introduced into Bruce4 C57BL/6 ES cells (14) via gene targeting. Correctly targeted ES cell clones were identified and then injected into goGermline blastocysts (15,16).…”
Section: Generation Of Bip-3xflag Micementioning
confidence: 99%
“…BiP-FLAG conditional knock-in mice were generated by targeting exon9 CDS region and flanking of with LoxP sites via gene targeting in Bruce4 C57BL/6 embryonic stem (ES) cells (14). Genetargeted ES cell clones were identified, and cells then injected into goGermline blastocysts (15,16). Male chimeric mice were bred with Flp female mice to delete the Neo cassette and establish heterozygous germline offspring on a C57BL/6 background ( Figure 1A).…”
Section: Generation Of Bip-flag Micementioning
confidence: 99%